Check- List of Birds of Indira Gandhi Nahar Project Stage- II (Rajasthan) - Soni, R. G. (Indian Forester, 1994)
The article describes the plant species and 170 bird species of scientific interest in studies of biodiversity chances from Indira Gandhi Nahar Project Stage-II, Rajasthan.